2007
DOI: 10.1111/j.1468-2494.2007.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro stability of triclosan in dentifrice under simulated use condition

Abstract: Triclosan has been formulated into a dentifrice at a 0.3% level to enhance the antibacterial function of the dentifrice, to improve oral health and to decrease the daily malodor inside the mouth cavity. The hypothesis that chloroform may be generated from triclosan when contacted with chlorinated drinking water has challenged our guarantee of safe use of triclosan in oral care products, especially in Colgate Total toothpaste. Currently, there was no available analytical method to detect chloroform levels under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…A study carried out by Fiss et al [ 78 ] described that TCS may involve in the generation of chloroform, under certain conditions can almost double the chloroform formation in the drinking water treated with chlorine. On the contrary, studies [ 79 ] showed that there was no production of measurable quantities of chloroform within a normal tooth-brush when using toothpaste containing TCS and normal chlorinated drinking water. According to US EPA classification, chloroform is a possible human carcinogen.…”
Section: Toxicity Of Tcsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out by Fiss et al [ 78 ] described that TCS may involve in the generation of chloroform, under certain conditions can almost double the chloroform formation in the drinking water treated with chlorine. On the contrary, studies [ 79 ] showed that there was no production of measurable quantities of chloroform within a normal tooth-brush when using toothpaste containing TCS and normal chlorinated drinking water. According to US EPA classification, chloroform is a possible human carcinogen.…”
Section: Toxicity Of Tcsmentioning
confidence: 99%
“…According to US EPA classification, chloroform is a possible human carcinogen. As a consequence, there was a campaign in UK underlining the potential of TCS to cause cancer, although Hao et al studies [ 79 ] revealed that the amount of chloroform generated was lower in volume. Meanwhile, TCS in household dishwashing soaps reacts with chlorinated H 2 O to produce significant quantities of chloroform, a probable human carcinogen [ 80 ].…”
Section: Toxicity Of Tcsmentioning
confidence: 99%
“…The antibacterial triclosan or 2,4,4垄-trichloro-2垄hydroxydiphenylether [101] is widely incorporated into oral care products particularly for halitosis treatment as it is highly compatible with other ingredients [102] and is stable [103] in various preparations [99,101]. Triclosan at a concentration of 0.3% reduced VSCs [104], and the calcium-based system was claimed to enhance this activity [101].…”
Section: Triclosanmentioning
confidence: 99%
“…9 Synthetic fertilizer can be an important source of nitrate in water and food. 10 The foods that often have the highest concentrations of nitrate, such as spinach, kale, and beets, often are touted for their nutritional benefits. The women in this study who were hardest hit by thyroid disorders tended to be better educated, physically active nonsmokers-a group Ward says is more likely to eat vegetables.…”
Section: Nitrate May Feed Thyroid Disordersmentioning
confidence: 99%
“…9 But another study published the same year showed no formation of detectable chloroform levels over a range of expected tooth-brushing durations among subjects using toothpaste with triclosan and normal chlorinated tap water. 10 Studies also have yielded conflicting findings regarding links between triclosan and adverse health effects in animals. One study, for example, associated exposure to low levels of triclosan with disrupted thyroid hormoneassociated gene expression in tadpoles, which encouraged them to prematurely change into frogs, 11 while another linked triclosan exposure with reduced sperm production in male rats.…”
mentioning
confidence: 99%